Análise combinatória e probabilidade: atividades pautadas com foco nos PCNs e no currículo da rede estadual - Oliveira, Gildo Gouveia de (2018)
This work aims to offer in detail teaching of Combinatorial Analysis and Probability, taking into account the National Curricular Parameters (NCP) and the Curricular Framework of the Sergipe State Network. We will present questions formulated from the above contents from news media using mathematical concepts in problem situations so that the teacher broadens and diversifies his teaching strategies, considering the abilities collected in the National High School Examination (ENEM).